2009
DOI: 10.3349/ymj.2009.50.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Haptoglobin in Patients with Premature Rupture of Membrane

Abstract: PurposeTo investigate whether allelic polymorphism of haptoglobin (Hp) is associated with premature rupture of membrane (PROM), the Hp phenotypes of pregnant women with PROM were analyzed.Patients and MethodsThe Hp phenotypes of 221 pregnant Korean women (187 control and 34 PROM patients) were determined by benzidine/hydrogen peroxide staining, following native polyacrylamide gel electrophoresis of hemoglobin-mixed sera. The Hp allele frequencies were calculated from the data of Hp phenotypes, and overall asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This highlights the need for large, prospective studies [21, 23]. Two small case-control studies examined the potential impact of Hp phenotype on other adverse pregnancy outcomes [19, 20]. Austrian women with gestational diabetes were more likely to have the Hp α 2 allele than women with uncomplicated pregnancies [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This highlights the need for large, prospective studies [21, 23]. Two small case-control studies examined the potential impact of Hp phenotype on other adverse pregnancy outcomes [19, 20]. Austrian women with gestational diabetes were more likely to have the Hp α 2 allele than women with uncomplicated pregnancies [19].…”
Section: Discussionmentioning
confidence: 99%
“…Austrian women with gestational diabetes were more likely to have the Hp α 2 allele than women with uncomplicated pregnancies [19]. In contrast, Korean women with premature rupture of membranes were more likely to have the Hp 1-1 phenotype (23% vs. 8%) than women with uncomplicated pregnancies [20]. The preeclampsia data suggest that these findings should be verified in large cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…63 Several studies have shown a relationship between martial metabolism and recurrent HSV-1 or/and HSV-2 manifestations. 6 17,22,[41][42][43][44][45] The different affinities of the three Hp phenotypes for Hb are relevant cofactors along with iron deficiency to explain differences in the susceptibility to Herpes virus. Moreover, it has been demonstrated that low levels of iron can decrease immune responses and favour reactivation of HSV.…”
Section: Discussionmentioning
confidence: 99%